Biological characteristics and classification of the thermophilic bacteria BML07 strain producing both thermostable amylase and cellulase isolated from my lam hot spring - Dinh Man, Tran; Kim Thoa, Nguyen; Thi Da, Nguyen; Quoc Viet, Nguyen (Vietnam Journal of Science and Technology, 2017)
The thermophilic bacteria strain BML07 was isolated from sedimental sludge of My Lam hot spring (Tuyen Quang province, Vietnam). Furthermore, this strain became promising candidate due to its capable of producing thermostable enzymes such as cellulase and amylase. The biophysiological characteristics of this strain revealed the optimal conditions for growth at pH 7.5; 2 - 3% NaCl, and 70 oC, however it is still able to survive at 80 oC. Observation of colony resulted in round shape and white, its cells obtained rod-shape (0.4 - 0.6 µm × 1.3 - 1.5 µm), positive Gram. Therefore, this strain was classified continuously based on Kit API 50/CHB as well as sequence of 16S rRNA. According to the taxonomical results using APIWEB software, the strain BML07 is similar of 97 % as Geobacillus caldoxylosilyticus (AY608950), however the sequence of 1500 bp fragment coding for 16S rRNA indicated that the homologous sequence between this strain and Geobacillus caldoxylosilyticus (AY608950) strain raised up to 99.8 %, as hence its own named Geobacillus caldoxylosilyticus BML07